Real-world safety of linaclotide in Chinese patients with irritable bowel syndrome with constipation: a multicenter, single-arm, prospective observational study - Yinglian Xiao; Xianmei Meng; Qingfeng Luo; Xiaohua Hou; Jie Jin; Xianfei Zhong; Wei Gong; Xiuling Li; Minhu Chen (Therapeutic Advances in Gastroenterology)
Background: Linaclotide, a guanylate cyclase-C agonist, is indicated for irritable bowel syndrome with constipation (IBS-C). However, real-world data on the safety and patient-reported outcomes (PROs) of linaclotide are scarce in Chinese patients with IBS-C. Objectives: To assess the real-world safety and PROs of linaclotide in the Chinese IBS-C population. Design: Multicenter, prospective observational study. Methods: Adults with IBS-C who had taken or planned to take at least one dose of linaclotide 290 μg were enrolled and followed up for 3 months. Face-to-face visits were conducted at baseline (V1), Week 4 ± 7 days (V2), and Week 12 ± 7 days (V3). Primary endpoints included the incidences of adverse events (AEs), AEs by severity, adverse drug reactions (ADRs), serious AEs (SAEs), and AEs leading to treatment interruption, discontinuation, and death. Secondary endpoints included mean treatment satisfaction at V2 and V3, and mean overall Irritable Bowel Syndrome-Quality of Life (IBS-QoL) at V2. Results: Out of 3000 enrolled patients, 2963 took at least one dose of linaclotide and were analyzed. Overall, 712 patients (24.0%) reported 1095 AEs, which were mostly mild (89.9%). Diarrhea, reported in 297 out of the 2963 patients analyzed (10.0%), was the most common AE. No severe diarrhea was reported. Totally, 319 patients (10.8%) reported ADRs. Forty-six patients (1.6%) reported 50 SAEs and two cases were considered related to linaclotide treatment. Fifty-one (1.7%) and 70 patients (2.4%) interrupted and discontinued treatment due to AEs, respectively. One patient died of hepatic cancer, which was considered unrelated to linaclotide treatment. During the follow-up, the mean (±SD) treatment satisfaction increased numerically and continuously (V1, 2.8 ± 1.3 ( n  = 1721); V2, 3.5 ± 1.1 ( n  = 1705); V3, 3.9 ± 1.0 ( n  = 833)). The mean (±SD) overall IBS-QoL increased numerically from 73.2 ± 16.6 ( n  = 1924) at V1 to 80.2 ± 15.5 ( n  = 1738) at V2. Conclusion: In the Chinese real-world setting, linaclotide was safe and well tolerated in patients with IBS-C. Numerically, there are trends toward improvement in PROs with linaclotide treatment.